Effects of cocoa-derived polyphenols treatment in regulating the adverse impacts of early-life stress in male and female mice. - Castro-Zavala, Adriana; Melgar-Locatelli, Sonia; Mañas-Padilla, María del Carmen; Rodríguez-Pérez, Celia; Castilla-Ortega, María Estela (My University, 2023)
Depression is one of the mental disorders that significantly affects today's society and calls for new treatments. In recent years, the gut microbiota has emerged as a key modulator of behaviour and mood due to the existence of the gut-brain microbiota axis. Environmental factors such as early stress or diet can negatively impact the predisposition to develop a mental disorder and the composition of the gut microbiota. Prebiotics are functional foods that stimulate the growth or activity of intestinal bacteria, providing benefits to the host's health. Polyphenols, such as those found in cocoa, possess prebiotic properties. Therefore, the consumption of polyphenols derived from cocoa could be a therapeutic pathway for mental disorders. Our study aimed to evaluate the impact of maternal separation with early weaning (MSEW) on depression and anxiety-like behaviours in male and female mice and neuroinflammatory markers in the brain. We also explore if the modulation of the gut microbiota through cocoa-derived polyphenols could ameliorate these behavioural and molecular alterations induced by early stress. Results showed higher immobility time in the tail suspension test in those mice exposed to MSEW and more depressive-like behaviour in females compared with males. Regarding results in the elevated plus maze, we found reduced travelled distance and time in open arms in MSEW mice. Additionally, we showed higher time in open arms in MSEW female mice treated with polyphenols than MSEW females that received a control diet, suggesting a reduction in anxiety like-behaviour. In conclusion, our findings support that early-life stress increases susceptibility to depression and anxiety-like behaviours in mice. Additionally, sex differences were observed, with females showing more pronounced depressive- and anxiety-like behaviour. Moreover, we highlight that modulation of gut microbiota could be a potential therapeutic target in mood disorders.
Keywords: Estrés (Fisiología); Cacao - Uso terapéutico - Ensayos; Polifenoles - Uso terapéutico - Ensayos; Early-life stress; Gut microbiota; Mice; Polyphenols